(untitled) (Journal of Dhaka Medical College, 2018)
Introduction: Dengue is now established as one of the most important Arboviral infection in tropical countries. As the epidemic continues worldwide, this Aedes mosquito-transmitted pathogen is considered a major re-emerging tropical disease and significant public health concern. The study was conducted to determine the sero-epidemiology and clinical picture of dengue virus infection among the clinically suspected patients attended in Dhaka Medical College Hospital during January to December 2016. Materials and Methods: The study was carried out on 145 clinically suspected Dengue patients attended in Dhaka Medical College Hospital from January to December 2016 who had fever with temperature >39°C. Blood sample was collected during acute febrile phase of patients and separated sera were tested for NS1 dengue antigen and IgM antibodies using commercial test kits (NS1 by OMC Healthcare (Pvt.) Ltd & IgM antibody by Omega Diagnostics Ltd.). Results: Of the total 145 patients 40 (27.6%) were positive for Dengue NS1 antigen and or IgM antibody test. Of the positive 40 patients, 18 (45%) were positive for NS1, 19 (47.5%) were positive for IgM and 3 (7.5%) were positive for both NS1 and IgM antibody. Major clinical manifestations were fever with arthralgia (79.5%) and retro-orbital pain (50%). Conclusion: Outbreak of Dengue fever is continuing every year and typical presentation of Dengue fever has changed. Arthralgia and retro orbital pain was the most common clinical feature in the present study instead of headache and rash with fever. A large number of suspected dengue cases were negative by Dengue tests for antigen NS1 and IgM antibody which suggests other organisms of similar clinical manifestations are becoming prevalent in Dhaka city. J Dhaka Medical College, Vol. 26, No.2, October, 2017, Page 111-116